On the nature of the supernatural - Tomc, Gregor (Teorija in praksa, 2019)
Religion is not a biological universal, an evolutionary adaptation characteristic of all individuals that benefits survival. It is a cultural universal that characterises all human societies. It is a spandrel, a chance side-effect of our adaptation to language. Since language is not an organ but a skill, it gradually developed in a co-evolutionary process, from exclusively specific to increasingly abstract use. In the analysis, the author argues that the capacity for religion emerges with concrete language, which enables man to construct imaginary behaviour with the aid of animism and anthropomorphism, fuelled by superstitious thinking in contingent situations. However, to create religious cognition, another ingredient is needed: transcendent experience with the help of hallucinations of the external world and incongruent bodily sensations.
Keywords: Nadnaravno; Religija; Religion; sociolingvistika; Supernatural; Transcendentalism; Transcendentalizem